Sedimentological and geochemical evidence for late quaternary environmental changes in southern Africa : a case study of the mudbelt deposits off Namaqualand - Mabote, Molefi Elliot (Department of Environmental and Geographical Science, 2015)
Bibliography: leaves 105-121.